PERANCANGAN APLIKASI JASA ANTAR JEMPUT LAUNDRY MENGGUNAKAN FRAMEWORK FLUTTER V. 3.3.10 BERBASIS MOBILE - Muhammad Fatwa Rizqi Alfarizi; Adam Sekti Aji (PPM Telkom University, 2023)
Washing is one of people's daily tasks that involves replacing dirty clothes with clean clothes, but not everyone can do it due to limited time, place to wash, and clothes. In addition, some weather factors can affect it. How quickly clothes dry depends on whether or not a washing machine is used. Pick-up service is a service that has been very helpful to the community because customers do not need to worry about the delivery of their goods. Laundry services are still very rare, which can cause difficulties for customers who do not have time to wash or bring it to the laundry. Overcoming the situation where customers have to deliver laundry themselves and solving the problems of previous research when the application only works on the Android operating system without knowing the location of the customer as well as problems with the Traditional Math payment system.